Determination of the association constant between the B domain of protein A and the Fc region of IgG1. (2nd April 2014) - Ansalone, P.; Abel, Marie‐Laure; Rossi, Antonella; Watts, John F.
<x xml:space="preserve">Abstract</x> The aim of this work is the numerical modelling of the binding mechanism between the Fc region of human IgG interacting with the B domain of Staphylococcal protein A (SpA). The comprehension of the involved kinetics is of noticeable impact for immunosensor diagnostic applications and consequently contributes to increase the sensitivity and efficiency of such devices based on the immobilization of antibodies on biosensor surface. Brownian dynamics methodology is applied to simulate the Fc–SpA encounter. Then, the association rates kon and koff are estimated from the analysis of the diffusional motion between the Fc region and the B domain of SpA combined with continuum electrostatic calculations. Therefore, the association constant Ka between Fc and SpA is calculated. The behaviour of Ka is analysed taking into account the relative distance between SpA and the Fc fragments. The analyses also include the effects on the binding affinity between SpA and Fc due to the variation of the solvent ionic strength and pH values. The association rates and their analyses are presented and discussed showing that the binding mechanism between the SpA and the Fc fragments is enhanced by the nonpolar interaction, while dissociation is driven by the electrostatic repulsion that occurs at relatively low pH. The numerical estimation of the association constant will support the definition of robust protocols for the detection of antibodies via protein A. Copyright © 2014 John Wiley & Sons, Ltd.